Relating 18F-FDG image signal-to-noise ratio to time-of-flight noise-equivalent count rate in total-body PET using the uEXPLORER scanner. (21st June 2022) - Leung, Edwin K; Abdelhafez, Yasser G; Berg, Eric; Xie, Zhaoheng; Zhang, Xuezhu; Bayerlein, Reimund; Spencer, Benjamin; Li, Elizabeth; Omidvari, Negar; Selfridge, Aaron; Cherry, Simon R; Qi, Jinyi; et al.
Abstract: Objective. This work assessed the relationship between image signal-to-noise ratio (SNR) and total-body noise-equivalent count rate (NECR)—for both non-time-of-flight (TOF) NECR and TOF-NECR—in a long uniform water cylinder and 14 healthy human subjects using the uEXPLORER total-body PET/CT scanner. Approach. A TOF-NEC expression was modified for list-mode PET data, and both the non-TOF NECR and TOF-NECR were compared using datasets from a long uniform water cylinder and 14 human subjects scanned up to 12 h after radiotracer injection. Main results. The TOF-NECR for the uniform water cylinder was found to be linearly proportional to the TOF-reconstructed image SNR 2 in the range of radioactivity concentrations studied, but not for non-TOF NECR as indicated by the reduced R 2 value. The results suggest that the use of TOF-NECR to estimate the count rate performance of TOF-enabled PET systems may be more appropriate for predicting the SNR of TOF-reconstructed images. Significance. Image quality in PET is commonly characterized by image SNR and, correspondingly, the NECR. While the use of NECR for predicting image quality in conventional PET systems is well-studied, the relationship between SNR and NECR has not been examined in detail in long axial field-of-view total-body PET systems, especially for human subjects. Furthermore, the current NEMA NU 2-2018 standard does not account for count rate performance gains due to TOF in the NECR evaluation. The relationship between image SNR and total-body NECR in long axial FOV PET was assessed for the first time using the uEXPLORER total-body PET/CT scanner.